How Climate Changes Affects Mosquito Vector Competence In Dengue Virus Spread: A Literature Review - Farizqi, Lintan Kurnia (Faculty of Medical - UPN Veteran Jawa Timur, 2024)
Background The impacts of climate change are currently increasing rapidly, largely due to greenhouse gas emissions from burning fossil fuels. Climatic conditions such as increased temperature, rainfall patterns affect the survival, development and geographical distribution of Aedes mosquitoes as well as their ability to transmit dengue virus known as vector competence. Dengue fever is transmitted by Aedes aegipty and Aedes albopictus mosquitoes. More than 10 million case if dengue fever have been reported. Climate change can accelerate the life cycle of mosquitoes, reducing the time it takes for the virus to develop inside the mosquito, increasing infection in the vector thus increasing the potential for dengue fever transmission. Methods This study uses the literature review method using the Google Scholar,Pubmed ans Science Direct databased using the keywords